Diagnostic Role of Bone Marrow Examination in Detecting Haematological and Nonhaematological Disorders (Medicine Today, 2019)
Introduction: Bone marrow study has wide application in clinical medicine. It is important test not only for diagnosis of haematological diseases but also for various systemic illnesses. The aim of this study is to determine the indications, the spectrum of haemotological and non haematological disorders diagnosed by using this procedure.Materials & Methods: It was a prospective study comprising 152 patients who underwent bone marrow examination for evaluation of haematological and nonhaematological disorders in the Department of Haematology, Enam Medical College Hospital during the period of 2012 to 2017.Results: In our study male to female ratio was 1.6:1 and common age group was >45years (n-65, 42.76%). Most common indications for bone marrow examination were pancytopenia (26.97%, n-41) and diagnosis of leukaemia/myeloproliferative neoplasm (25.66%, n-38). 90.13% (n-137) marrows were pathological. Non-malignant conditions were 40.79% (n-62) and malignant conditions were 49.43% (n-75). Non malignant haematological condition were 33.55% (n-51), malignant haematological conditions were 47.37% (n-72). Most common nonmalignant haematological conditions were aplastic anaemia (15.13%, n-23) and immune thrombocytopenic purpura (9.87%, n-15). Visceral leishmaniasis was found 3.29% (n-5). Acute myelogenous leukaemia (14.47%, n-22) and multiple myloma (11.18%, n-17) were the most common malignant haematological condition. Secondary deposit was found 1.97% (n-3).Conclusion: Bone marrow examination is a simple invasive procedure for diagnosis of both haematological and nonhaematological diseases when routine investigations failed to reach the final diagnosis.Medicine Today 2019 Vol.31(1): 15-18